Electrophysiology of Error Processing : Does the Error Positivity Have a Mirror Image Negativity? - Leland, David S.; LeBouton, Gabrielle M.; Moe, Simon M.; Reimer, Denee J.; Dortch, Sierra D.; Brandt, Lucas J.; Becker, Samuel J.; Beard, Katie L. (My University, 2018)
Electroencephalography (EEG) is a measure of brain electrical activity from the scalp with components, such as positive and negative deflections in the signal, indexing various mental processes. If the inversion reflects the negative end of a single dipole, one would expect stronger correlations between anterior and posterior sites for the time windows of the Pethan at other times (~125-325 ms). If the inversion is due to referencing, one would expect a more consistent correlation between anterior and posterior sites throughout the entire time window.
Color poster with text, charts, and graphs.
Keywords: Posters; Psychology; Electroencephalography